Water-temperature controlled deformation patterns in Heifangtai loess terraces revealed by wavelet analysis of InSAR time series and hydrological parameters - Cao, Zhongcheng; Wang, Teng (Frontiers in Environmental Science, 2022)
Loess deposits are widely distributed in western and central China. Because loess is wet- collapsible, loess mass is prone to failure after water infiltration. Heifangtai, composed of two adjacent typical loess platforms located in the Loess Plateau besides the Yellow River, has experienced hundreds of landslides in the past few decades. Here, we derive surficial time-series deformation, velocity, and amplitude of seasonality from the Sentinel-1 SAR images acquired from Oct 2014 to Mar 2021 in the Heifangtai region and study their relation with precipitation, temperature and irrigation applying wavelet analysis. The decomposed velocities show that not only a large amount of along-slope deformation occurred surrounding the terrace, but also a significant subsidence in the residential area in the middle of the platform. The high seasonality areas are distributed along the Yellow River and on the terrace consistency with other water sources, e.g., springs and irrigation, revealing a promotion of periodic water-involved process on deformation in loess. Through the wavelet analysis we find that the temperature is almost in-phase with the uplift velocity when the temperature is below frozen point. The precipitation precedes the surface displacement of ~ 1 to 2 months for water penetration. The comparison between irrigation volumes and averaged displacements suggests that irrigation also plays a role in promoting subsidence from March to October but uplift in winter due to frost heave. We highlight that the retrogressions of the terraces in this region maybe accelerated by both the natural and anthropogenic factors. Careful monitoring and water management are highly recommended for the safety of local residences and infrastructures.